Improving Young Learners’ Vocabulary Skills By Using Busy Book Media With Guessing Games Strategy - natasya malindo putri ching (ENJEL: English Journal of Education and Literature, 2024)
The learning media is everything related to facilities and infrastructure (tools/objects) are used to support or to facilitate the delivery of subjects in the learning process to achieve the goals of learning itself. Teachers can use learning media to convey lesson information to students and can stimulate students’ attention, feelings, thoughts, and willingness to learn in order to encourage an effective learning process. Busy book is one of the learning media in teaching in English. “Busy book” is a book made of flannel which contains interesting pictures. This book is very safe for students so that it can be used freely, and has a soft flannel texture and the fabric doesn’t get wet easily so this book can last a for a long time. The purpose of this research is to find out the effectiveness of using busy book media using the guessing game strategy to improve the vocabulary mastery of grade 3 students at SDN 1 Wringinpitu in the 2022/2023 academic year. This research is Action Research carried out in teaching and learning activities in class, so this research includes Classroom Action Research. The result is the guessing game technique can improve students’ vocabulary skills. The results of this action research in the second cycle also prove the action hypothesis that the use of busybooks with guessing games can improve the English vocabulary skills of grade 3 students at SDN 1 Wringinpitu in the 2022/2023 academic year.